2013
DOI: 10.1007/s11414-013-9368-5
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Tailored Depression/Suicide Prevention in Latino Youth: Community Perspectives

Abstract: Latino adolescents are at elevated risk for depression and suicide compared to other ethnic groups. Project goals were to gain insight from community leaders about depression risk factors particular to Latino adolescents and generate innovative suggestions to improve cultural relevance of prevention interventions. This project utilized a CBPR approach to enhance cultural relevance, acceptability, and utility of the findings and subsequent program development. Two focus groups of youth and youth-involved Latino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Focus group participants indicated the need to find outlets to communicate their feelings. This is consistent with previous research showing that art therapy reduces trauma-related symptoms in adolescents (Lyshak-Stelzer, Singer, and Chemtob, 2007), and that creative engagement helps foster social connection in adolescent Latinas (Ford-Paz et al, 2015). Licensed art, music, and dance therapists use these media to help participants express their feelings.…”
Section: Life Is Precious™ Program and Evaluation Developmentsupporting
confidence: 92%
“…Focus group participants indicated the need to find outlets to communicate their feelings. This is consistent with previous research showing that art therapy reduces trauma-related symptoms in adolescents (Lyshak-Stelzer, Singer, and Chemtob, 2007), and that creative engagement helps foster social connection in adolescent Latinas (Ford-Paz et al, 2015). Licensed art, music, and dance therapists use these media to help participants express their feelings.…”
Section: Life Is Precious™ Program and Evaluation Developmentsupporting
confidence: 92%
“…Building successful mHealth programs for Latinos requires that messages be accurate, relevant, and respectful of patients' cultural norms. 12,24,25 Per the Centers for Disease Control and Prevention, mHealth programs that are able to achieve this are more likely to be impactful than those that do not deliver messages in a culturally sensitive and language-specific manner. [26][27][28] Similarly, messages will need to take into consideration values and attitudes surrounding illness for this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide prevention programs in Spanish are also lacking, which is concerning given that about 34% of Hispanics do not speak English proficiently in the U.S. [47]. Importantly, Hispanic youth and community leaders have suggested that culturally tailored depression/suicide prevention interventions for Hispanic youth should: (1) utilize multiple strategies (e.g., public awareness/educational outreach, skill-building activities) that are sustainable, (2) seek to raise awareness about depression in culturally meaningful ways, and (3) promote social connection and cultural enrichment activities [48].…”
Section: Suicide Prevention Interventions Among Hispanicsmentioning
confidence: 99%